2023
DOI: 10.2478/rjim-2023-0001
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine efficacy in patients hospitalized with COVID-19 pneumonia: a systematic review and meta-analysis

Abstract: Background: N-Acetylcysteine (NAC) is a mucolytic agents with anti-inflammatory properties that has been suggested as an adjunctive therapy in patients with COVID-19 pneumonia. Objectives: We conducted a systematic review and meta-analysis to evaluate available evidence on the possible beneficial effects of NAC on SARS-COV-2 infection. Methods: In September 2022, we conducted a comprehensive search on Pubmed/Medline and Embase on randomized controlled trials (RCTs) and observational studies on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…15 Need for ICU admission and invasive ventilation was 0.86 of OR (95% CI 0.44-1.69) and 0.91 of OR (95% CI 0.54-1.53), respectively. 15 Based on the results obtained from a meta-analysis, the authors suggested the certainty of evidence about the use of NAC for the treatment of patients with COVID-19 was very low; thus, the authors did not recommend the routine use of NAC for patients with COVID-19 in clinical practice. 15 Based on the absence of benefits from both meta-analyses, 10,15 it is hard to suggest the routine use of NAC in the management of patients with COVID-19.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…15 Need for ICU admission and invasive ventilation was 0.86 of OR (95% CI 0.44-1.69) and 0.91 of OR (95% CI 0.54-1.53), respectively. 15 Based on the results obtained from a meta-analysis, the authors suggested the certainty of evidence about the use of NAC for the treatment of patients with COVID-19 was very low; thus, the authors did not recommend the routine use of NAC for patients with COVID-19 in clinical practice. 15 Based on the absence of benefits from both meta-analyses, 10,15 it is hard to suggest the routine use of NAC in the management of patients with COVID-19.…”
mentioning
confidence: 94%
“…15 Based on the results obtained from a meta-analysis, the authors suggested the certainty of evidence about the use of NAC for the treatment of patients with COVID-19 was very low; thus, the authors did not recommend the routine use of NAC for patients with COVID-19 in clinical practice. 15 Based on the absence of benefits from both meta-analyses, 10,15 it is hard to suggest the routine use of NAC in the management of patients with COVID-19. Furthermore, one study also failed to support the role of NAC for patients with COVID-19, even the study has conducted to use inhalation route.…”
mentioning
confidence: 99%
See 3 more Smart Citations